Preparation and characterization of thermal neutron sensitive lithium doped polystyrene plastic scintillators - ZHANG Kaihui; LI Xiang; DENG Mingxue; SHI Yun; ZHOU Qi; WANG Ke; CHEN Junfeng (He jishu)
BackgroundLithium-doped plastic scintillators possess the dual-mode detection capability for both fast and thermal neutrons, and combine the advantages of conventional plastic scintillators such as cost-effectiveness and the ability to fabricate in large sizes, have drawn much attention and shown great potential for thermal neutron detection in recent years.PurposeThis study aims to prepare large, trasparent polystyrene (PS) plastic scintillators doped with lithium methacrylate (LiME) via a thermal polymerization method, and to characterize their optical transmittance, luminescence, and pulse height spectrum response properties.MethodsThe composition, and structure of synthesized LiME were analyzed using Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, and spectrophotometry. The transmittance, photoluminescence (PL) and X-ray excited luminescence (XEL) properties of LiME-doped plastic scintillators were measured and compared with those of pure plastic scintillator. The pulse height spectra (PHS) under excitation of gamma-ray were measured to determine values of the relative light output for the plastic scintillator by using Compton Edge calibration.ResultsThe optimal concentrations of AIBN, PPO, and POPOP for polystyrene plastic scintillators were experimentally determined to be 0.1 wt%, and 0.02 wt%, respectively. Characterization results indicate that the LiME-doped plastic scintillators maintain excellent optical quality, with the peak position of the emission spectrum remaining consistent with that of the pure plastic scintillator. However, as the LiME content increases, both the fluorescence intensity and light output of the scintillator gradually decrease. This trend is presumed to be associated with fluorescence quenching effects induced by the doping process.ConclusionsLarge, transparent plastic scintillators doped with up to 12 wt% LiME (equivalent to 0.9 wt% Li) can be successfully synthesized using a thermal polymerization method. While the performance of lithium-doped plastic scintillators still requires further improvement, these materials hold great potential for applications requiring efficient dual-mode detection of both fast and thermal neutrons.